SAVI Approach Paper 4: Thinking and Working Politically - Supporting p artners and staff through a participatory apporach to political econom y analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We s upport staff and partners to analyse the power relations that shape ch ange in their state, and to use this knowledge to inform their decisio n-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...